European Union energy policy in the 21st century: a process of riskification - Dekeyrel, Simon (2023)
In the 1990s, the European Union (EU) took the first important steps towards a common energy policy. Aided by the extraordinarily favourable environment of the end of the Cold War, it developed an energy policy around a model heavily inspired by the fundamental principles of European integration laid down in the Treaty of Rome in 1957, centred on the use of regulatory tools to build and maintain competitive markets. At the turn of the century, the market optimism that had enabled European integration to re-engage with its roots after the relative obscurity of the European Communities in the energy domain in the previous decades, quickly waned. It gradually became clear that the EU’s most important energy partner, Russia, was not willing to play by EU rules. As successive gas supply disruptions in the second half of the 2000s shocked Europe, energy security rose to the top of the European political agenda. As such, the energy domain also regained significant amounts of scholarly attention. How did the energy policy of the EU react to an increasingly adverse environment; did it stick to its market-oriented approach, or did it adjust and adapt in function of the changing international environment? To answer this question, scholars have primarily relied on traditional concepts in European integration studies (e.g. the regulatory state) and dichotomous theoretical frameworks (e.g. liberalism vs. realism). As a consequence, existing research has often been unable to formulate more precise answers, which fully express the complexities of the developments in the European energy dimension. By offering an original conceptualisation of the contemporary evolution of European energy policy on the basis of a blended theoretical approach and an interdisciplinary methodology, this research aims to remediate this gap in the academic literature. Drawing on insights from International Political Economy (IPE) and securitisation theory and methods from political science and the legal discipline, it will argue that the current mode of energy governance can be understood as a result of a successful process of riskification. Specifically, it will demonstrate that the European Commission has consistently framed European import dependence as a risk to security of supply since the early 2000s, in order to legitimise the establishment of supranational precautions aimed towards mitigating that alleged risk. These “riskifying moves” have been accepted by the relevant audience, the member states, resulting in the adoption of a variety of precautionary measures to safeguard EU security of supply. This intersubjective understanding of import dependence in terms of risk and the associated recalibration of EU internal and external energy policy in turn radically altered the dynamic of the EU’s relations with Russia and Gazprom. This research aims to improve the theoretical understanding of the contemporary evolution of European energy governance, which better captures its current intricacies. It also has significant practical relevance. In light of the dramatic geopolitical turmoil caused by the Russian invasion of Ukraine in February 2022, it can serve as a valuable comparative tool to assess the discursive and policy developments in the European energy dimension.